Subcontractor Selection Review Industry XYZ With Analytic Network Process (ANP) Method - Septian, Ardianto (IPTEK Journal of Proceedings Series, 2020)
In the steel construction of the Kendari Newport Container Facilitiy and Utilities Project's which was undertaken by the XYZ Contractor, there was a problem. Until the contractor issued a warning letter against the selected subcontractor because of delays in work. This research aims to examine the stages of selection subcontractors whether there is an error in decision making that causes delays work by subcontractor that selected as a partners.Therefore, decision makers need right selection methods. Multi Criteria Decision Making (MCDM) method is an appropriate method for the selection of several criteria. One of them is the Analytic Network Process (ANP) -Risk Assessment method.Based on the analysis using the ANP method ,sub-criteria with the highest priority weight is the bid price with a weight of 17.13%, The final results of the overall analysis showed that subcontractor B get in first place with a score 2,97. In this research subcontractor B has the highest value, which means that the subcontractor is feasible and accordance with the assessment of XYZ Company to be a partner to doing the steel construction work in this case study